Benign breast diseass - antiprophyliferative therapy - T.V. Ovsyannikova (LCC «Medicine-Inform», 2018)
Benign breast diseass - antiprophyliferative therapy T.V. Ovsyannikova RUDN University, Moscow, Russian Federation Benign breast diseases (BBD) include all kinds of diffuse and focal mastopathy, and diffuse mastopathy is the most common one. The hormone-dependent proliferation is induced mainly by the active metabolites of estrogen. Metabolites of estradiol are its two hydroxy-derivatives: 2-hydroxyestrone (2-ONE1) and 16α-hydroxyestrone (16α-OHE1), their ratio is crucially important for the development of proliferative processes in the mammary glands. The diagnosis of BBD is based on a detailed analysis of the patient's complaints, features of her history, visual assessment, results of palpation and instrumental examination methods (ultrasound and mammography). Drug therapies for BBD include the drugs with a direct effect on altered breast tissues. Currently, the innovative preparation Indinol® Forto is actively used. The drug has a wide range of antitumor activity. It shows a mild anti-estrogenic effect and normalizes the hormonal balance, causes selective death of breast cells with abnormally high proliferative activity, suppresses fibrosis and inflammation. The article presents the results of a randomized, double-blind, placebo-controlled multicenter study in which Indinol® Forto was used in patients with cyclic mastodynia against benign mammary dysplasia. Key words: benign breast diseases, mastopathy, breast cancer, estrogen, mammary gland, Indinol® Forto. For citation: Ovsyannikova T.V. Benign breast diseases - antiprophyliferative therapy. Russian journal of Woman and Child Health. 2018;1(1):-70.